Análise da gestão na fundação Amazonprev à luz da ética - Bett, Geneci Behling (2013)
This paper presents a brief study, supported by theoretical references, of the management model of the Amazonprez Foundation, in the light of ethical principles to verify if there is an alignment of the administrative decisions, backed by the Ethics Code, and if these are coherent with the ethical actions within the public institution. The first chapter deals with some concepts and theories about ethics based on great theoretical references. It analyzes some important situations such as the ethical being and human dignity as a formative element a restlessness as to the way an individual should act, behave, with regard to the individual aspect as well as to the company aspect, and how he/she can work or show his/her values in the face of the social context, its personal and interpersonal relations. In the second chapter, company ethics is also dealt with, with the goal of showing that the business organizations, even while going through changes or restructuring processes, can act in an ethical and transparent way in their management model. In chapter three, ethical management is dealt with in the context of public institutions. The analysis categories will be developed, pari passu, during the theoretical review which the scholar will carry out, of the two central and structuring themes of the study, that is, organizational management and ethics. Based on the definitions and concepts extracted from seminal texts of authors of the two theoretical lines, the scholar will construct the theoretical reference mark, which, therefore will not be defined, a priori.